5(x+2)-2x=11

Simple and best practice solution for 5(x+2)-2x=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+2)-2x=11 equation:


Simplifying
5(x + 2) + -2x = 11

Reorder the terms:
5(2 + x) + -2x = 11
(2 * 5 + x * 5) + -2x = 11
(10 + 5x) + -2x = 11

Combine like terms: 5x + -2x = 3x
10 + 3x = 11

Solving
10 + 3x = 11

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + 3x = 11 + -10

Combine like terms: 10 + -10 = 0
0 + 3x = 11 + -10
3x = 11 + -10

Combine like terms: 11 + -10 = 1
3x = 1

Divide each side by '3'.
x = 0.3333333333

Simplifying
x = 0.3333333333

See similar equations:

| x/6-2=6 | | x(1-x)(1-3x)=0 | | 2x+5+x+120=180 | | 3x+1-(x+8)=10x-4 | | ab*bc*c=3 | | 3x^2-xy-2y^2+12=0 | | 10-x=4+2x | | 6x^3=36x^2 | | ln(5x-4)+2=0 | | 5(c+3)=-10 | | 12=2b-1 | | =m(4+p)+p(3+m) | | 20x^3-12x^2=0 | | 4(c-6)+5c=57 | | 4+(5-b)=7 | | 3(a+7)=33 | | 2x+20=x-18 | | 3+x+x-6=x | | 5x+6-3x=x+20 | | 2x^3-12x^2+19x-6=0 | | 6m-2=m+12 | | (x+3)(x-8)(x-2)=0 | | y=x^3+27 | | 2400=22x+10y | | 4sqrtx+-3=19 | | 4sqrtx-3=19 | | x+2y-1=0 | | 0.21=logx | | 4x+12=42-2x | | 16(x+1)=-4(x+14) | | 6x+11=9x-4 | | x-3y+4=0 |

Equations solver categories